ANALISIS KESIAPAN GURU DALAM MENYUSUN PEMBELAJARAN JARAK JAUH (PJJ) DI MASA PANDEMI COVID-19 - Marselinus Jheni Jacob; Imanuel Sairo Awang; Munawar Thoharudin (STKIP Persada Khatulistiwa Sintang, 2021)
This study aims to analyze the readiness of primary school teachers in Compiling Distance Learning (PJJ) during the Covid-19 Pandemic. This study is motivated by the importance of the readiness of primary school teachers in facing the Covid-19 pandemic, namely by implementing Distance Learning (PJJ) in the learning process. This study involved primary school teacher respondents and the principal of SD Negeri 17 Mungguk. Data in the form of teacher opinions and statements were collected using questionnaires and interviews and completed with documentation. Furthermore, the collected data were analyzed descriptively. The results showed that theoretically, the teacher already had an understanding of Distance Learning, but it was still lacking in implementation. The motivation of teachers in implementing learning innovations is very high, this is supported by facilities, facilities and infrastructure. School readiness in implementing Distance Learning is included in the high category, elementary school teachers have high expectations regarding their task of implementing Distance Learning during the Covod-19 Pandemic, because this will have a positive impact on the quality of learning.